Finanzmärkte und (soziale) Nachhaltigkeit – ein schwieriges Verhältnis - Christian Hecker (Wirtschaftsdienst, 2016)
Die Finanzmarktregulierung ist auch eine Frage sozialer Nachhaltigkeit. Ist sie unzureichend, können Ungleichgewichte verschärft werden: privaten Gewinnen stehen dann soziale Verluste gegenüber. Trotz der Finanzmarktkrise profi tieren Vermögende stärker von Anlagen auf den Finanzmärkten. Deren Regulierung sollte sich auf eine bessere Gläubigerhaftung, die Vermeidung von Moral Hazard sowie die Bekämpfung von Too-big-to-fail-Problemen und kurzfristig orientierten Vergütungssystemen konzentrieren. – – In the catalogue of "Sustainable Development Goals" approved by the UN General Assembly in September 2015, financial market regulation is mainly described as an issue of social sustainability. This classification is appropriate because inadequate regulation leads to imbalances between profits and liability, as private gains are accompanied by social costs. Consequently, the distribution of wealth and income deteriorates inasmuch as people with high fortunes tend to have more opportunities to benefit from investments in capital markets. Financial market regulation, aiming to prevent such a development, should mainly focus on fighting moral hazard, limiting too-big-to-fail problems and banning short-term-oriented remuneration structures in banks.
Keywords: G18; G20; G28; 330; Finanzmarktregulierung; Wirkungsanalyse; Vermögen; Vermögensverteilung; Gläubiger; Haftung; Moral Hazard; Bank; Betriebsgröße